중학교 축구선수의 체격 및 기초체력 평가 기준 개발 : 경기도를 중심으로 - 정연성; Yeon-sung Jung; 석진수; Jin Su Suk; 강성기; Seoung Ki Kang (Ch'eyuk kwahak yŏn'gu, 2024)
[목적] 본 연구의 목적은 중학교 축구선수의 체력과 기초체력 평가 기준을 개발하여, 현장의 지도자에게 훈련과 선수 육성의 기초차료를 제공하는데 있다. [방법] 연구대상자는 중학생 축구선수 총 440명(1학년 178명, 2학년 132명, 3학년 130명)로 선정된 대상자에 대해 7가지 체격, 10가지 기초체력 항목에 대한 측정을 진행하였다. 수집된 측정결과는 Windows Excel 2021을 이용해 정리하고, Windows SPSS 26.0을 이용해 기술통계를 실시하였다. 이후, 측정결과의 기술통계 결과를 바탕으로 Cajori 5단계 상대평가 방법을 적용하여 학년과 체력요소별 평가 기준치를 설정하였다. [결과] 연구결과를 통해 측정된 자료를 기반으로 중학교 축구선수에게 적절한 학년과 체격 및 기초체력 측정 항목별 평가 기준치를 설정하여 제시하였다. [결론] 본 연구결과를 통해 축구와 중학교 학생의 학년별 체격 및 체력특성이 반영된 평가 기준치를 설정할 수 있었다. 이를 바탕으로 현장의 지도자가 선수의 선발, 육성을 위한 훈련 목표치 설정과 부상 예방과 재활 효과 등의 분야에 다양하게 활용할 수 있을 것으로 기대된다. PURPOSE This study aimed to develop physique and basic physical fitness evaluation criteria for middle school soccer players, providing a foundation for training and player development to be used by coaches in the field. METHODS The study involved 440 middle school soccer players (Grade 1=178, Grade 2=132, and Grade 3=130). Measurements were conducted on seven physique and ten basic physical fitness factors. Measurement results were organized using Windows Excel 2021 and descriptive statistics were performed using Windows SPSS 26.0. Based on the descriptive statistics of the measurement results, the Cajori 5-Grade evaluation method was applied to establish evaluation criteria for each grade and fitness component. RESULTS The study results provide evaluation criteria for middle school soccer players based on the measured data, considering grade, physique, and basic physical fitness. CONCLUSIONS The criteria established in this study are expected to be widely utilized by coaches in the field to set training goals for areas such as player selection, development, injury prevention, and rehabilitation.